Utilization of LMS G-Site with Independent Learning Flow to Improve Critical Thinking Ability on Respiratory Materials - Parjiyo, Parjiyo; Lisdiana, Lisdiana; Saptono, Sigit (Universitas Negeri Semarang)
Independent Learning is an educational process that guides students to develop according to their nature to achieve safety and happiness. One of the characteristics of Pancasila student profiles is critical thinking, in the hope that students can mobilize and develop physical and spiritual strength in accordance with nature, era, and society.This happens because education does not provide the widest possible space for students. There needs to be a LMS G-Site with Independent Learning Flow to improve critical thinking skills. This study aims to analyze the use of the LMS G-Site with the Independent Learning flow to improve the critical thinking skills of high school students on the subject of human respiration. This study is conducted using Research and Development (R&D) model. The research design was carried out using the ADDIE development research design. The characteristic of LMS-G-Site is that there is an Independent Learning flow where in each flow, materials, learning videos and tasksin differentiated learning are provided. The use of the LMS G-Site with Independent Learning Flow is reflected in the post-test score (90.08%) which is higher than the pre-test score (63.83%) and the N-gain test result is 76% in the high category. As for student learning outcomes based on assignments as much as 80.43% of students got an assignment score in the very good category and as many as 19.57% students got an assignment score in the good category. Thus the LMS-G-Site with Independent Learning Flow can be used as an alternative to improve students' critical thinking skills based on knowledge and students’ skills in differentiated learning aspects.